Diversity, Distribution and Phylogeny of Hesionidae (Annelida) Colonizing Whale Falls: New Species of Sirsoe and Connections Between Ocean Basins - Shimabukuro, Mauricio; Carrerette, Orlemir; Alfaro-Lucas, Joan Manel; Rizzo, Alexandra Elaine; Halanych, Kenneth M.; Sumida, Paulo Yukio Gomes (Frontiers in Marine Science, 2019)
Whale falls are important environments contributing to biodiversity, connectivity and evolutionary novelty in deep-sea ecosystem. Notwithstanding, most of this knowledge is based in studies from NE Pacific basin. Interestingly, the only known natural whale fall on the SW Atlantic has faunal composition affinities with carcasses from other deep-ocean basins. In this carcass, annelid worms belonging to Hesionidae are abundant and species-rich, and include some shared species with NE Pacific Ocean. Here we evaluate the diversity of Hesionidae on the SW Atlantic using new information of implanted whale bones and explore whether some species have interbasin distribution or if they represent cryptic species in different basins. We described, using morphological and molecular data, a total of 10 new hesionid species and report of a new lineage Sirsoe ‘BioSuOr’, not formally described herein. Two hesionids found exclusively in deep-sea chemosynthetic environments, Sirsoe Pleijel, 1998 and Vrijenhoekia Pleijel, Rouse, Ruta, Wiklund & Nygren, 2008, are primarily distinguished from each other by the presence of a median antenna on the former and its absence on the latter. However, our analyses showed that Vrijenhoekia should be synonymized with Sirsoe and for this reason we emended the diagnosis of Sirsoe. We also emphasized the presence of Sirsoe balaenophila comb. nov. and S. sirikos in SW Atlantic whale falls confirming their interbasin distribution. Moreover, COI and 16S rDNA data reveal that S. balaenophila comb. nov. also comprises cryptic species on the SW Atlantic (S. pirapuan sp. nov. and S. ypupiara sp. nov) and perhaps also in the Pacific Ocean (herein named as S. balaenophila lineage-2). The new species, S. maximiano, is shared between whale falls from SW Atlantic and vent sites from Mid-Cayman Spreading Center. Our data adds to the growing literature showing species are shared between deep ocean basins and among cognate deep-sea environments.